2022
DOI: 10.1186/s12979-022-00272-1
|View full text |Cite
|
Sign up to set email alerts
|

Ageing attenuates bone healing by mesenchymal stem cells in a microribbon hydrogel with a murine long bone critical-size defect model

Abstract: Background Despite the high incidence of fractures and pseudoarthrosis in the aged population, a potential role for the use of mesenchymal stem cells (MSCs) in the treatment of bone defects in elderly patients has not been elucidated. Inflammation and the innate immune system, including macrophages, play crucial roles in the differentiation and activation of MSCs. We have developed lentivirus-transduced interleukin 4 (IL4) over-expressing MSCs (IL4-MSCs) to polarize macrophages to an M2 phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…We also quantified the non-leukocyte (CD45 - ) population, including chondrocytes (CD45 - , Sox9 + ), endothelial cells (CD45 - , CD31 + ), and muscle satellite cells (CD45 - , Pax7 + ). Chondrocytes were not detected in any of the samples, which is similar to our previous studies using this model [ 9 , 36 , 37 ]. Very few endothelial cells and muscle satellite cells were detected on Day 7.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We also quantified the non-leukocyte (CD45 - ) population, including chondrocytes (CD45 - , Sox9 + ), endothelial cells (CD45 - , CD31 + ), and muscle satellite cells (CD45 - , Pax7 + ). Chondrocytes were not detected in any of the samples, which is similar to our previous studies using this model [ 9 , 36 , 37 ]. Very few endothelial cells and muscle satellite cells were detected on Day 7.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have suggested that crosstalk among different types of cells may collectively contribute to the bone healing process [ [36] , [37] , [38] , [39] ]. We therefore sought to elucidate cell compositions in tissues from bone defect sites that contained either the MSCs-embedded scaffold or the bone graft and compare them with that of the original bone graft.…”
Section: Resultsmentioning
confidence: 99%
“…Bone defects caused by various traumas and diseases have become one of the most common clinical diseases [ 1 ]. At present, bone transplantation is the main method to solve the repair of bone defects [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12,20,21,53,54] However, existing microribbons and microfibers produced using the wet spinning technique consist solely of polymers. [12,53,[55][56][57][58] There is currently no research available on microribbons or microfibers composed of a combination of polymers and insoluble inorganic biomaterials. This gap in knowledge may be attributed to the fact that traditional wet spinning techniques involve injecting a precursor solution into a cross-linking solution through a needle.…”
Section: Discussionmentioning
confidence: 99%